APLIKASI BS RUTEKU, NAVIGASI BLOK SENSUS MENGGUNAKAN ALGORITMA DJIKSTRA - Muna, Muna; Kusmaiwanto, Herry (MATEMATIKA, 2017)
The activities of the Badan Pusat Statistik (BPS) in conducting the census and survey generally begin with the tracing of the census block (BS) by using map map print-out census blockÂ If the officer gets a new working area he / she knows not too many officers who have difficulty to block the census of his working area and in determining its boundaries. Error determining the location or limits of the selected Censusblock is a Major Error, for that BS Ruteku as a tool of navigation fast and cheap, because it does not need to connect to the internet and does not make the battery run out quickly. The method used in BS Ruteku application uses Djikstra Algorithm method. This application is designed with the aim to find the route of the nearest road from one area to another. The Ruteku BS Application is the result of the Censusblock Digit Map Overlay with Indonesian Basic Map (http://navigasi.net/goptd.php), which added some Local Content and uses the android / GPS navigation system as the Navigator Engine. To be able to provide the Shortest Distance, Fastest Distance or Distance straight, then the existing Polyline autoruting process. The test results show that the accuracy of the use of the earth map is reliable, this application is also able to find the nearest route from a region or census block and can provide direction through the sound.